The Scenarios of Sub-District Health Promoting Hospitals in the Next Decade (A.D. 2011- 2021) - Khamfaeng, Charoenchai; Chaisena, Malee; Khamrat, Chaiyong (Journal of Health Science of Thailand, 2017)
This research was aimed at studying the scenarios of sub-district health promoting hospitals in the next decade (A.D. 2011-2021) using EDFR(Ethnographic Delphi Futures Research). The key informants consisted of 20 experts; the study was conducted from June 26, 2011 to February 20, 2012 using purposive sampling. The research tools included semi-structured interviews and questionnaires; statistics employed were percentage, mean, standard deviation, median, mode, interquartile range and content analysis. The findings indicated 8 prospects. 1) Roles of the public health officers would be more work on prevention against non-communicable diseases and employment of family medicine in a more proactive fashion. 2) Public participation would be more involvement in selfcare requisites. 3) Equipment and durable supply would be standardized. 4) Human resource management would be focused more on adeptness at management and administration, epidemiology, leadership. 5) Organization structure would be nurse practitioners in all the hospitals, and the personnel system would include all 5: registered nurse, executive of sub-district health promoting hospital, public health technical officer, community health officer, and dental hygienist. 6) Budget sources and management would be increasingly funded by National Health Security Office (NHSO), Social Security Office, Office of Permanent Secretary (Ministry of Public Health), and private donations. 7) Academic development would be concerned with public health personnel with minimum educational requirements of bachelor’s degree and a shift of focus on participatory action research. 8) Information technology of the hospitals would deal with computers as the central tools of community data storage. Therefore, The government should encourage people to contribute more on their own health care.